Methods in bioengineering : cell transplantation - Soto-Gutierrez, Alejandro; Navarro-Alvarez, Nalu; Fox, Ira J. (Artech House, 2011)
This practical book is part of the new Artech House Methods in Bioengineering series - volumes designed to offer detailed guidance on authoritative methods for addressing specific bioengineering challenges. Written and edited by recognized experts in the field, each book provides research engineers, scientists, and students with step-by-step procedures, clear examples, and effective ways to overcome problems that may be encountered. This unique volume covers in detail the basic techniques and protocols of regenerative medicine, focusing on methods for cell transplantation. You explore a wide range of critical factors, such as grown tissues, cells, laboratory-made compounds, and engineered organs. The books helps you understand the many intricate steps involved in tissue engineering, cell isolation, progenitors and stem cell differentiation, and in vivo models for assessing new strategies. Publisher abstract.
Keywords: Cell transplantation.; Biotechnology.; Regenerative medicine.; Bioengineering.; elektronické knihy; electronic books